Examining the impact of e-government service process on user satisfaction. (7th August 2018) - Sachan, Amit; Kumar, Rajiv; Kumar, Ritu
Abstract : Purpose: A government website is considered as an electronic government service delivery system (eGSDS). The authors look at this eGSDS from its process point of view. This study aims to expand the existing knowledge of e-government adoption, and to identify the significance of eGSDS process to user satisfaction. Design/methodology/approach: This study uses a quantitative technique using data collected from 197 respondents. Structure equation modeling has been used to test the model and the proposed hypotheses. Findings: The findings indicate that as the eGSDS process improves, a user's perception of the government website's ease of use increases, leading to increased perceived usefulness, which increases user satisfaction. The findings also indicate that eGSDS process has a significant impact on perceived usefulness and user satisfaction. This study provides evidence that the technological capabilities embedded in the government website processes are an important factor in determining e-government service quality and ultimately e-government user satisfaction. Research limitations/implications: The sample used was sufficient for this study and allowed reasonable conclusions to be drawn, but cannot be considered representative of all e-government users in India. Further research may help to validate the findings and generalize the results to a wider population. This study extends the current literature that looks at e-government adoption. Academicians and information systems researchers may use these findings for further research. Practical implications: The research provides evidence that the technological capabilities embedded in the eGSDS process are critical in adopting e-government services. Government or concerned agencies may consider eGSDS process attributes (e.g. navigation, searching and transacting) while designing e-government service to give improved experience to its user. Originality/value: E-government websites have become an important point of contact with citizens for many public services. However, more study is needed to understand how Web-based technological capabilities of e-government services affect user satisfaction. This study is an attempt to explore the impact of the eGSDS process on e-government user satisfaction.